Allylic Acetals as Acrolein Oxonium Precursors in Tandem C−H Allylation and [3+2] Dipolar Cycloaddition. (3rd June 2019) - Lee, Heeyoung; Kang, Dahye; Han, Sang Hoon; Chun, Rina; Pandey, Ashok Kumar; Mishra, Neeraj Kumar; Hong, Sungwoo; Kim, In Su
Abstract: The ruthenium(II)‐catalyzed C−H functionalization of (hetero)aryl azomethine imines with allylic acetals is described. The initial formation of allylidene(methyl)oxoniums from allylic acetals could trigger C(sp 2 )−H allylation, and subsequent endo ‐type [3+2] dipolar cycloaddition of polar azomethine fragments to deliver valuable indenopyrazolopyrazolones. The utility of this method is showcased by the late‐stage functionalization of bioactive molecules such as estrone and celecoxib. Combined experimental and computational investigations elucidate a plausible mechanism of this new tandem reaction. Notably, the reductive transformation of synthesized compounds into biologically relevant diazocine frameworks highlights the importance of the developed methodology. Abstract : Effizienter Gerüstbau : Eine Ru II ‐katalysierte C‐H‐Allylierung von (Hetero)arylazomethiniminen mit Allylacetalen, gefolgt von einer intramolekularen endo ‐artigen dipolaren [3+2]‐Cycloaddition, ermöglicht den direkten, effizienten Aufbau hoch substituierter Indenopyrazolopyrazolon‐Gerüste in guten bis hohen Ausbeuten.